Cytomegalovirus retinitis following corticosteroid overdose for Vogt-Koyanagi-Harada disease - Khochtali, Sana (Indian J Ophthalmol, 2020)
A 33-year-old patient was diagnosed with acute Vogt-Koyanagi-Harada (VKH) disease and was prescribed prednisolone (1 mg/kg/day) and azathioprine (2.5 mg/kg/day). She mistakenly took an excessively high dose (4 mg/kg/day) of prednisolone for 14 days. The erroneous dose of corticosteroids was progressively corrected. Several weeks after initial presentation, the patient developed a polymerase chain reaction-proven bilateral cytomegalovirus retinitis, with extensive occlusive arteritis in the right eye. Systemic immunosuppressive therapy was temporarily discontinued and viral retinitis was successfully managed with systemic and intravitreal ganciclovir. Corticosteroids were reintroduced to control recurrent VKH disease. Final visual acuity was 20/1000 in the right eye and 20/50 in the left eye.